Canada-wide Survey of Canadian Scientiests:: A Preliminary Report on the State of the Discipline, the Fossil Fuel Industries and Environmental Science - Miall, Charlene; Miall, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY A survey of Canadian earth scientists has yielded important information concerning their attitudes in four key areas relevant to the future of geoscience in Canada. First, most respondents agree that traditional geology departments in Canada are shifting their primary focus from the science of exploration and extraction of resources to environmental science and environmental remediation. Second, a majority believe that fossil fuel industries are perceived by the general public as contributors to global warming. Notably, most respondents also support the implementation of programs to mitigate the effects of these emissions. Third, in terms of the relevance of earth science to the study of climate change, although a majority responded that climate change, over the last few decades, has been driven by a combination of natural and anthropogenic processes, most also agreed that explanations for this climate change have not adequately taken paleoclimate data into consideration. Finally, in terms of the role of science and advocacy in informing public policy, a significant majority of respondents felt that public understandings and media representations of climate change are not based on good scientific knowledge and that politicians are more influenced by public opinion than science. Most respondents felt that earth scientists need to become more active in speaking out about social problems and their solutions. An agenda for change should include the development of public position statements on issues of national importance, and a public education campaign about the work of the geoscience community.